The impact of the mandatory adoption of International Financial Reporting Standards in Portugal - Anastasova, Tatyana Kostadinova (2013)
This dissertation provides insight into the mandatory implementation of IFRS in Portugal by 2005 and a contribution by highlighting the main features of this process. The motivation of this research is a recent reform in Portuguese accounting rules. Based upon a review of the content of the 2005 financial statements presented by the Portuguese listed companies, we found a high degree of variability among the disclosures either regarding the narrative explanations of transition or reconciliations disclosures. The findings indicate positive total impact on the net income and negative total effect on the shareholders‟ equity. The individual adjustments show discrepancy between the two set of standards (PGAAP and IFRS) in the accounting treatment of business combination, employee benefits, share-based payments, investment property and property, plant and equipment with reference to both net income and shareholders‟ equity. Furthermore IFRS 1 supplies optional exemptions to the general principle of retrospective application in some areas and we investigate the choices made by the Portuguese listed firms. The results show that IFRS 1 options are not used to offset the impact of mandatory adjustments on equity. This study is relevant to the preparers, auditors and users of the financial information in identifying the most problematic areas of implementation of IFRS.